Construction of diagnostic solution with the use of non-digital expert estimates - Рябчук, Н. Г.; Журавльова, Л. А. (Proceedings of National Aviation University (archive), 1999)
Considered is the technology of construction of group of experts estimation in case- the individual experts estimation is not digital. In this case the technology of construction of group estimation is illustrated by indicated on the diagrams of term-multiplicities and base scales of chosen linguistic variables. Received is logical model and the results of program realization